Hodgkin Lymphoma Untreated for Six Years Presenting with Tracheoesophageal Fistula - Jason R. Westin; Amye Gibbs; Keith R. Mills; Sattva S. Neelapu (Case Reports in Medicine)
Hodgkin lymphoma is a highly curable cancer with modern therapy, with five-year survival rates in excess of 80%. However, the natural history of the untreated disease is largely unknown. We present the case of a patient with Hodgkin lymphoma who went untreated for over 5 years due to patient choice. Eventually, the patient developed hypoxemia, significant weight loss, and a tracheoesophageal fistula. After a placement of a gastrostomy tube and tracheal stent, treatment with standard chemotherapy was initiated. The patient achieved an excellent response, the fistula closed without further intervention, and there is no evidence of relapse six years later. Even in a patient with significant Hodgkin-lymphoma-related sequelae, standard therapy can result in excellent long-term outcomes.